2021
DOI: 10.5817/cp2021-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in virtual reality with a muscular avatar influences performance on a weightlifting exercise

Abstract: Virtual Reality (VR) technology can be used to influence performance on endurance exercises. In this study, we focused on manipulating perception of own-body strength by exercising in VR as a muscular avatar. In this repeated-measure study, twenty-nine participants performed biceps curl exercise in a maximum repetitions protocol, up to exhaustion. The exercise was done either in VR as a muscular avatar, or without VR, in front of the mirror. Dependent variables were the number of exercise repetitions and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The sense of embodiment is usually subdivided in to three sub-components, the senses of self-location, agency and ownership. These perceptual elements have been found to impact the user experience in diverse ways, such as the feeling of being present in the VE [100], the perception of the environment [11], behaviors inside and outside the VE [23,98], task performances [5,25] or cognitive load [73]. Hence, we present here a discussion based on previous results reported in the literature for different avatar's dissimilarity types, regarding the sense of embodiment.…”
Section: Impact Of Dissimilar Avatars On the Sense Of Embodimentmentioning
confidence: 93%
See 1 more Smart Citation
“…The sense of embodiment is usually subdivided in to three sub-components, the senses of self-location, agency and ownership. These perceptual elements have been found to impact the user experience in diverse ways, such as the feeling of being present in the VE [100], the perception of the environment [11], behaviors inside and outside the VE [23,98], task performances [5,25] or cognitive load [73]. Hence, we present here a discussion based on previous results reported in the literature for different avatar's dissimilarity types, regarding the sense of embodiment.…”
Section: Impact Of Dissimilar Avatars On the Sense Of Embodimentmentioning
confidence: 93%
“…For example, Yee and Bailenson found that being embodied in a taller avatar can alter the user's confidence in a negotiation task, and that the avatar attractiveness could alter intimate behaviors [122]. Among others, it was also shown that being embodied inside an avatar seen as creative improved ideas' fluency and originality inside and outside the VE [37]; that an opposite gender's avatar could alter gender-stereotypical beliefs about one's own personality [108], and that being presented with a more muscular avatar could increase the number of repetitions in a weightlifting exercise [23]. Peck et al also found that the Proteus effect could be used to alleviate stereotype threats [86], a phenomenon wherein one feels at risk to confirm a stereotype about her/his social group, which might lead to cognitive underperformance [106].…”
Section: The Proteus Effectmentioning
confidence: 99%
“…A muscular avatar coincided with lower heart rates and perceived effort compared to medium or nonathletic avatars. Similarly, participants completed more repetitions in a weightlifting exercise when embodying a muscular avatar in VR than when exercising in front of a mirror (Czub & Janeta, 2021). These effects may be explained by the theory of the minimal self (Gallagher, 2000), which consists of a sense of body ownership and a sense of agency.…”
Section: Embodiment and Visual Feedback In Virtual Realitymentioning
confidence: 94%
“…However, these findings refer to passive movement and may not apply to loco-motion. Once again, existing research focuses on avatar configuration (Czub & Janeta, 2021;Kocur et al, 2021;Kocur, Kloss, Schwind, Wolff, & Henze, 2020).…”
Section: Psychological Components Of Exercisementioning
confidence: 99%
“…In strength training, researchers have investigated the use of VR for resistance exercises, such as weightlifting [34], and found that VR can provide a more varied and engaging workout experience and also provide real-time feedback on form and technique, which can help individuals avoid injury and optimize their performance [35]. Balance training using VR technology has also been investigated, with studies examining the effects of VR on postural stability and proprioception [36][37][38][39][40].…”
Section: -1-vr Exercisementioning
confidence: 99%